2003
DOI: 10.1155/s1565363303000219
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antitumor Activity ofcis‐bis(acylthioureato) platinum(II) Complexes, cis‐[PtL2] [HL1=N,N‐Diphenyl‐N′‐Benzoylthiourea or HL2=N,N‐diphenyl‐N′‐(p‐nitrobenzoyl)thiourea]

Abstract: A low-molecular weight chromium-containing fraction of the material resulting from dichromate reduction by bovine liver homogenate was investigated by NMR and ES-MS. The ES-MS spectrum showed a readily detectable peak at m/z 786.1. The same molecular weight reasonably agreed with the relatively low diffusion coefficient measured by NMR-DOSY experiments on the main species observed in the 1H NMR spectrum. At least two downfield shifted and broad paramagnetic signals were apparent in the 1H NMR spectrum. Tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 2 publications
(4 reference statements)
2
10
0
Order By: Relevance
“…As shown in Table 4, the palladium (II) and platinum (II) complexes were more cytotoxic (IC 50 = 0.08–12.46 μ M) than their respective ligands. These results reveal that the cytotoxic activity increases dramatically when ligands are coordinated to the metal ion [18, 19, 32]. …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 4, the palladium (II) and platinum (II) complexes were more cytotoxic (IC 50 = 0.08–12.46 μ M) than their respective ligands. These results reveal that the cytotoxic activity increases dramatically when ligands are coordinated to the metal ion [18, 19, 32]. …”
Section: Resultsmentioning
confidence: 99%
“…The free ligands present an intense band in the region between 1800 and 1610 cm -1 , which is assigned to vC=O stretching vibrations [28,29,55] and is absent in the spectra of the complexes, evidencing …”
Section: Infrared and Ultraviolet-visible Spectroscopymentioning
confidence: 99%
“…The complexes exhibit νRu-P stretching in the range 521-511 cm -1 . Also, the νRu-S, νRu-N and νRu-O stretching vibrations occur as weak bands in a region of low intensity at about 500-350 cm -1 [55].3.4 Multinuclear 31 P{ 1 H}, 1 H and 13 C NMR experimentsIn the 1 H NMR spectra of the free ligands, a shoulder band corresponding to a singlet of the N-H group proton is observed in the region of 8.10-8.70 ppm[28,29,50]. This kind of signal is absent in the spectra of the complexes, indicating the deprotonation of the acylthioureide group by the coordination of the ligand, which acts as a monoanionic species, to the metal.…”
mentioning
confidence: 99%
“…It has been reported that substituted acylthiourea ligands might act as monodentate sulfur donors, bidentate oxygen and nitrogen donors. They could also coordinate through the keto-or enolthione form, depending of the ligands themselves, and the metal ions and counter-anions used [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%